Simple µ-solid phase extraction using c18 film for the extraction of polycyclic aromatic hydrocarbons in coffee beverage - Loh, Saw Hong; Neoh, Pei Ee; Tai, Chee Tung; Kamaruzaman, Sazlinda (Malaysian Society of Analytical Sciences, 2018)
Polycyclic aromatic hydrocarbons (PAHs) are produced as by-products in the coffee roasting process. A simple and efficient micro-solid phase extraction (µ-SPE) procedure coupled with high performance liquid chromatography and fluorescence detection has been developed for the simultaneous analysis of selected PAHs, namely phenanthrene (PHE) and benzo[a]pyrene (BaP) in coffee beverage. The method offered trace detection limits in the range of 0.003 to 0.1 µg/L and good relative recovery average in the range of 88.3 to 95.7%. The µ-SPE procedure has been simplified by employing C18 film as an adsorbent. The method is beneficial in terms of rapidity, simple operation, in-expensive, consumption of micro volumes of solvent and biodegradable agarose film as the adsorbent holder. The method was then applied to analyse five coffee beverage samples and the results indicated the presence of BaP in the range of 1.0 to 1.9 µg/L.